Mild and Convenient Synthesis of Benzodithiazoles by Oxidative Cyclization of Bis(thiobenzanilides) - Hassan, Zahid; Langer, Peter (Synlett, 2012)
Benzodithiazoles were prepared by oxidative cyclization of bis(thiobenzanilides). The reactions were performed at room temperature under mild conditions and rely on the use of N-benzyl-DABCO tribromide.
Keywords: benzodithiazoles; thioamides; organic ammonium tribromides; cyclization; C–S bond formation